Process for alkylating toluene with methanol to form styrene using a low sodium content potassium/cesium modified zeolite catalyst composition - 223394 Liu, Huei Cheng
A process for alkylating toluene (or derivative thereof) with methanol to form e.g. styrene and ethhylbenzene (or derivatives thereof) using a modified low sodium content zeolite catalyst composition is disclosed. The zeolite catalyst composition is exemplified by a type X- Y- zeolite modified with potassium and cesium through a sequential exchange.